(3SGfMGJ Oej GdbUQ aj eWGQMGJ Hfj GdYUQs - (3eMeO Hf CMeO GdWGdhj GdCQJbj GdOeTbj, CHh GdeYGdj,J (B1014 (3g` s ((3EHQGgje Hf MSjf Hf CHj GdThGQH s)
(3ChdgG (B:s
(3hHYO aEf dHYV JMH GdcdGe hCf GLeY eGJaQb ef Jdc GdeQGSdGJ hGdeWGQMGJ fGXekG eG EfJKQ ef YbhOgG HjO GdTJGJ s
(3BNQgG (B:s
(3heG cJHJ CjVkG , hGfG HGOjGQ GdQhejI , cJGH GdhRjQ GdYXe hGdOSJhQ daNe Ydi HGTG hbO MUd Yf bOhe LdhS GdSdWGf CMeO Hf GdSdWGf eMeO hYRI GdOgQ bO CVGAJ HTeS YOd LdJ QLi Gdge s
(3SfI (B1321 (3g` Yf fSNI HOGQ GdcJH GdNOjhjI ecJhHg SfI (B1065 (3g` s
(3fSNI KGfjIs
(3JJab ai ChdgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX cJHJ decJHg CMeO JjehQs
(3HChdgG agQS Hbde eJCNQ dHYV ehVhYGJgs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdCOHs